GAMBARAN AUDIOGRAM PADA PASIEN TB-MDR DI RSUP DR. HASAN SADIKIN BANDUNG: AUDIOGRAM PROFILE OF MDR-TB PATIENTS IN HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Hilman, Anton; wijana, Wijana; Anggraeni, Ratna (RSUP Dr. Kariadi, 2021)
BACKGROUND: Multidrug-resistant tuberculosis (MDR TB) is a disease condition of TB that resistant to isoniazid and rifampin, with or without resistance to other anti-tuberculosis drugs. An important problem arising from MDR TB therapy is the ototoxicity associated with use of aminoglycosides. Monitoring of hearing function is important to evaluate ototoxic effects. OBJECTIVE: This study was conducted to determine the audiogram profile in MDR-TB patients who received kanamycin therapy in Dr. Hasan Sadikin General Hospital Bandung METHODS: A retrospective descriptive study with a cross sectional design was conducted on MDR TB patients at Dr. Hasan Sadikin General Hospital Bandung (RSHS) Bandung. The inclusion criteria of this study is all medical records of MDR TB patients at the MDR TB polyclinic RSHS Bandung in the period January 1 - December 31 2018. Exclusions criteria were a history of tympanic membrane perforation, congenital ear abnormalities, hearing loss before therapy, and incomplete medical record data. RESULTS: There were 97 patients in the study sample. MDR TB mostly affects the 18–34 year age group. At the end of the first month of therapy, audiogram changes were found in 9.3% of patients and in the fourth month, 22.7% of patients have sensorineural hearing loss with varying degrees. CONCLUSION: Changes in the audiogram profile have occurred at the end of the first month of MDR TB therapy which is characterized by sensorineural hearing loss.